Willa Cather's Pittsburgh - Bintrim, Timothy W.; Jaap, James A.; Vanderlaan, Kim (University of Nebraska Press, 2021)
"Cather Studies, Volume 13 explores the myriad ways that Willa Cather's writing career was shaped during the crucial years in Pittsburgh and the artistic, professional, and personal connections she made there"-- Provided by publisher
Keywords: Cather, Willa, -- 1873-1947 -- Knowledge and learning.; Cather, Willa, -- 1873-1947; Pittsburgh (Pa.); Pittsburgh (Pa.) -- In literature.; LITERARY CRITICISM -- Women Authors.; Pennsylvania -- Pittsburgh; Literature; Learning and scholarship